A Study of RelatÄ±onship between Perceived OrganÄ±zational Justice and Individualism Collectivism Values Among Academic Staff - ESEN, Åžaban; KARADEMÄ°RAslÄ± Ã‡Ä°LLÄ°OÄžLU (Journal of Economics and Behavioral Studies, 2014)
The purpose of this study is to investigate the relationship between the individualsâ€™ perceptions of justice in the organizations they work in and the personality tendencies of individualism or collectivism they have. For that reason, firstly the concept of organizational justice and the values of collectivism and individualism were explained; their relationship was mentioned through theoretical and empirical studies in the literature. As measurement tool, survey method was used. The surveys were conducted on 133 academicians working at Bartin University which is one of the state universities in Turkey. As a result of doing reliability analysis and factor analysis, the last form of scale was given. The perceived organizational justice handled in the scale was composed of three dimensions which are distributive justice, procedural justice and interactional justice; and despite individualism and collectivism have four sub-dimensions (horizontal individualism, vertical individualism, horizontal collectivism and vertical collectivism) this was not taken into account in the study and they were discussed from only individualism and collectivism dimensions. In consequence of ANOVA analyses performed, it is found that there is a low relation between collectivism value and distributive justice as well as between individualism value and interactional justice. The findings of ANOVA analysis showed that in the demographic characteristics only the title variable groups showed significant differences between interactional justice and individualism. By multi-regression analysis, it is seen that as much as procedural justice increases the exhibited collectivism characteristic increases, in similar way as much as distributive justice increases the collectivism characteristic increases. There was no obvious significant correlation between individualism variable and justice dimensions.